A Stereotype Threat Account of Boys' Academic Underachievement. Issue 5 (12th February 2013) - Hartley, Bonny L.; Sutton, Robbie M.
Abstract : Three studies examined the role of stereotype threat in boys' academic underachievement. Study 1 (children aged 4–10, n = 238) showed that girls from age 4 years and boys from age 7 years believed, and thought adults believed, that boys are academically inferior to girls. Study 2 manipulated stereotype threat, informing children aged 7–8 years ( n = 162) that boys tend to do worse than girls at school. This manipulation hindered boys' performance on a reading, writing, and math test, but did not affect girls' performance. Study 3 counteracted stereotype threat, informing children aged 6–9 years ( n = 184) that boys and girls were expected to perform similarly. This improved the performance of boys and did not affect that of girls.